выполняется для любых х и у, значит левая и правая части равны
(x + a)² -(y + 3)² = x² + 2ax + a² - y² - 6y - 9
(x + y + 7)•(x - y + b) = x² - xy + bx + xy - y² + by + 7x - 7y + 7b = x² + bx - y² + by + 7x - 7y + 7b
x² + 2ax + a² - y² - 6y - 9 = x² + bx - y² + by + 7x - 7y + 7b
2ax - bx - 7x - 6y - by + 7y + a² - 9 - 7b = 0
коэффициенты при x y и свободном члене равны
получили систему
2a - b - 7 = 0
-6 - b + 7 = 0
a² - 9 - 7b = 0
из первого
2a - b = 7
выполняется для любых х и у, значит левая и правая части равны
(x + a)² -(y + 3)² = x² + 2ax + a² - y² - 6y - 9
(x + y + 7)•(x - y + b) = x² - xy + bx + xy - y² + by + 7x - 7y + 7b = x² + bx - y² + by + 7x - 7y + 7b
x² + 2ax + a² - y² - 6y - 9 = x² + bx - y² + by + 7x - 7y + 7b
2ax - bx - 7x - 6y - by + 7y + a² - 9 - 7b = 0
коэффициенты при x y и свободном члене равны
получили систему
2a - b - 7 = 0
-6 - b + 7 = 0
a² - 9 - 7b = 0
из первого
2a - b = 7